Effects of blockade of endogenous Gi signaling in Tie2‐expressing cells on bone formation in a mouse model of heterotopic ossification. Issue 8 (20th May 2015) - Wang, Liping; Carroll, Dylan O'; Liu, Xuhui; Roth, Theresa; Kim, Hubert; Halloran, Bernard; Nissenson, Robert A.
ABSTRACT Available evidence indicates that some Tie2‐expressing (Tie2+) cells serve as multipotent progenitors that have robust BMP‐dependent osteogenic activity and mediate heterotopic ossification (HO). Since signaling through the G protein Gi is required for cell motility, we hypothesized that blockade of endogenous Gi signaling in Tie2+ cell populations would prevent HO formation. Blockade of Gi signaling in Tie2+ cells was accomplished in transgenic mice with expression of pertussis toxin (PTX) under the control of the Tie2 promoter (Tie2+/PTX+). Bone formation within HOs was evaluated 2 weeks after BMP injection. Expression of PTX in Tie2+ cells significantly reduced the bone volume (BV) of HOs in male and female mice. Orthotopic bones were assessed at the distal femur and expression of PTX significantly increased trabecular bone fractional volume and bone formation rate in females only. In adult Tie2+/GFP+ mice, GFP+ cells appeared both inside and at the surfaces of bone tissue within HOs and in orthotopic bones. In summary, blockade of Gi signaling in Tie2+ cells reduced the accrual of HOs and stimulated osteogenesis in orthotopic bones. Targeting of Gi protein coupled receptors in Tie2+ cells may be a novel therapeutic strategy in states of abnormal bone formation such as osteoporosis and HO. © 2015 Orthopaedic Research Society. Published by Wiley Periodicals, Inc. J Orthop Res 33:1212–1217, 2015.